A novel variant of ER-alpha, ER-alpha36 mediates testosterone-stimulated ERK and Akt activation in endometrial cancer Hec1A cells - Wang Zhao-Yi; Wang Zhen-Bo; Liang Xing-Wei; Yan Li-Ying; Lin Sheng-Li; Qiao Jie; Schatten Heide; Sun Qing-Yuan (BMC, 2009)
Abstract Background Endometrial cancer is one of the most common gynecologic malignancies and its incidence has recently increased. Experimental and epidemiological data support that testosterone plays an important role in the pathogenesis of endometrial cancer, but the underlying mechanism has not been fully understood. Recently, we identified and cloned a variant of estrogen receptor (ER) alpha, ER-alpha36. The aim of the present study was to investigate the role of ER-alpha36 in testosterone carcinogenesis. Methods The cellular localization of ER-alpha36 was determined by immunofluorescence. Hec1A endometrial cancer cells (Hec1A/V) and Hec1A cells with siRNA knockdown of ER-alpha36 (Hec1A/RNAi) were treated with testosterone, ERK and Akt phosphorylation was assessed by Western blot analysis. Furthermore, the kinase inhibitors U0126 and LY294002 and the aromatase inhibitor letrozole were used to elucidate the pathway underlying testosterone-induced activities. Results Immunofluorescence shows that ER-alpha36 was localized on the plasma membrane of the both ER-alpha- and androgen receptor-negative endometrial cancer Hec1A cells. Testosterone induced ERK and Akt phosphorylation, which could be abrogated by ER-alpha 36 shRNA knockdown or the kinase inhibitors, U0126 and LY294002, and the aromatase inhibitor letrozole. Conclusion Testosterone induces ERK and Akt phosphorylation via the membrane-initiated signaling pathways mediated by ER-alpha36, suggesting a possible involvement of ER-alpha 36 in testosterone carcinogenesis.